Are people willing to share their political opinions on Facebook? Exploring roles of self-presentational concern in spiral of silence. (November 2017) - Liu, Yu; Rui, Jian Raymond; Cui, Xi
Abstract: Social networking sites such as Facebook have become a major platform for American political discussion. However, publicly expressing opinions on Facebook can make individuals perceived negatively by their Facebook friends, contributing to the spiral of silence. The purpose of this study is to extend the spiral of silence framework by integrating the perspective of online self-presentation to investigate the psychological processes of Facebook users' political self-disclosure through commenting, sharing and posting behaviors. Survey data from 283 Facebook users confirmed the opinion-congruence based mechanism argued by the classic spiral of silence theory, and found that Facebook users' willingness of online engagement in controversial issues is also related to self-presentational concern and approval-based contingency of self-worth. Highlights: Psychological processes of SNS users' political self-disclosure are examined. An extended spiral of silence model with a self-presentation approach is proposed. The opinion-congruence based mechanism argued by spiral of silence is confirmed. Approval-based CSW and self-presentational concern explain online expression. Two opposing dialectics of opinion expression on SNSs are discussed.